2018
DOI: 10.1039/c8ee01642a
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride graphdiyne as a free-standing electrode displaying ultra-stable and extraordinary high Li storage performance

Abstract: Bottom-up fabrication of fluoride graphdiyne offers a versatile approach to the rational design of ultra-stable flexible 2D electrode materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
124
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(126 citation statements)
references
References 49 publications
2
124
0
Order By: Relevance
“…Duringt he chargep rocess, the Fi ons are close to the carbocation and thus will reconstruct the semi-ionic CÀF bonds. [11] The CV shows that fluorinated MXenem aterials have differente lectrochemical properties. In fact, the FMX3 sample shows the electrochemical signatures of TiF 3 ,w hich was shown to be presentb ym eans of XPS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Duringt he chargep rocess, the Fi ons are close to the carbocation and thus will reconstruct the semi-ionic CÀF bonds. [11] The CV shows that fluorinated MXenem aterials have differente lectrochemical properties. In fact, the FMX3 sample shows the electrochemical signatures of TiF 3 ,w hich was shown to be presentb ym eans of XPS.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that during the discharge process, with the translation of C−F bonds from semi‐ionic to ionic, the F ions are bonded to Li ions through electrostatic interactions. During the charge process, the F ions are close to the carbocation and thus will reconstruct the semi‐ionic C−F bonds . The CV shows that fluorinated MXene materials have different electrochemical properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lithium ion batteries (LIBs) are becoming the most widely used energy storage devices owing to the relatively high energy density and low self‐discharge . Now, with endless pursuit of energy density, as exemplified by the cruise mileage of electric vehicles and the standby time of smartphones, the energy upgrade of cathode and anode materials is urgently required . Although the employment of high nickel oxide cathode and silicon–graphite composite anode has pushed the energy density of cells over the threshold of 300 Wh kg −1 , new chemistry is necessary for the next generation LIBs with an energy density over 300 Wh kg −1 .…”
Section: Introductionmentioning
confidence: 99%